Agricultural mechanization policy options in Rwanda - Takeshima, Hiroyuki; Benimana, Gilberthe Uwera; Spielman, David J.; Warner, James (International Food Policy Research Institute, 2024)
This paper summarizes general demand- and supply-side issues for agricultural mechanization based on recent studies that focus on experiences and evidence from both Africa and Asia. The paper pro vides typologies of agricultural mechanization in Rwanda along with policy options within the context of its current mechanization support strategies. Provincial variations in agroecology and cropping systems, irrigated/rainfed systems, farm size, and labor use intensity, among other factors, characterize the key types of mechanization use in Rwanda. Support for mechanization in Rwanda can be broadly tailored to (a) irrigated medium-scale farmers in the Eastern province and Kigali; (b) rainfed medium-scale farmers in the Eastern and Southern provinces; (c) rainfed, small-scale highland farmers in the Northern province; and (d) irrigated small-scale farmers in the Western province. Recent experiences in other countries with rugged terrain and smallholder farming systems similar to Rwanda suggest that significant growth in the use of tractors is possible in the medium term among smallholders cultivating rainfed maize and legumes, in addition to irrigated rice. However, farm wages may still be too low in Rwanda and tractor-hiring fees may still be too high to induce a shift to mechanization in the short term. Therefore, it may be advisable for policy support for mechanization to focus on improving the understanding of mechanization needs among each type of farmers identified, knowledge of suitable machines, and required skills for their operations and maintenance. Such efforts should also balance the need to develop competitive markets and supply networks for promising machines, parts, and repair services at a viable and integrated market scale.